Estudo Teórico de bicamadas híbridas - Silva, Thiago de Sousa (2013)
In the present work, we use first principles calculation based on density functional theory, as implemented in the SIESTA code, to investigate the modifications in the electronic properties of hybrid bilayers composed of two monolayersof graphene with a nanodomain of B3N3, due to strain. The calculations were made with two different approximations for the exchangecorrelation functional, the Generalized Gradient Approximation (GGA) and Van der Waals Density Funcional (VDW-DF). Six types of configuration for the bilayers were made: three configurations with the stacking of the bilayer with the atoms of one layer on top of the atoms of the second layer (like h-BN) and three configurations with the stacking of the bilayer with the atom of one layer on top of the center of the hexagon of the second layer (like graphite). The three configurations for the two types of stacking are: AA, where the atoms of B and N stay on top atoms of B and N respectively, AB, where atoms of B and N stay on top of atoms of N and B respectively and AC, where atoms of B and N stay on top of atoms of C. The investigation of the structural stability of the nanostructures was based in the calculations of the formation energy, interaction energy and cohesive energy. The results shows that the structure with configuration 2 AA is more stable, and also conductive. We can observe that the two approximations used in the calculations show the same results for the electronic properties of all structures. The studies of the effects of the strain were made only in the structure that has shown itself as more stable. The role of the strain was made through the variation of the distance between the monolayers. Through these studies we can identify the distance between monolayers for which the structure is more stable. This distance has shown itself different for the two approximations. The opening of the energy gap due to strain was possible in the calculations using the GGA approximation, but the same did not happened in the calculations using the VDW-DF approximation.